Effect of taurine intervention on oleic acid-induced primary hepatocyte steatosis in orange-spotted grouper (Epinephelus coioides) - Xiao, Ruyi; Feng, Hanmo; Niu, Xingjian; Bai, Fakai; Ye, Jidan (Archives of Biological Sciences, 2021)
Paper description: Control of metabolic syndrome in cultured fish is needed to counteract the increase in fatty liver. An oleic acid-induced primary hepatocyte steatosis model in grouper was established to investigate effects of taurine intervention in liver lipid metabolism. Transcriptome hepatocyte analysis was used to identify differentially expressed genes and construct a metabolic network of taurine in lipid metabolism. Differentially expressed genes are involved in primary bile acid biosynthesis, glycerophospholipid metabolism, glycerolipid metabolism, fatty acid elongation. Taurine intervention affected the expression of identified genes. Taurine plays a regulatory role in lipid metabolism improving the functioning of steatosis hepatocytes. Abstract: Examination of the molecular mechanism of taurine regulation of lipid metabolism in fish is limited. In this study, an oleic acid (OA)-induced hepatocyte steatosis model of orange-spotted grouper (Epinephelus coioides) was established for the first time. The model was used to test the effect of taurine on steatosis hepatocytes in Control, High-fat (0.4 mM OA) and Taurine (0.4 mM OA + 2 mM taurine) experimental groups of fish. Hepatocyte samples were subjected to transcriptome analysis. A total of 99634 unigenes was assembled, 69982 unigenes were annotated and 1831 differentially expressed genes (DEGs) in Control vs High-fat group, and 526 DEGs in the High-fat vs Taurine group were identified, of which 824 DEGs (Control vs High-fat) and 237 DEGs (High-fat vs Taurine) were observed to be upregulated, and 1007 DEGs (Control vs High-fat) and 289 DEGs (High-fat vs Taurine) were downregulated after taurine intervention. These genes are involved in peroxisome proliferator-activated receptor (PPAR) and 5' AMP-activated protein kinase (AMPK) signaling pathways, fatty acid elongation, primary bile acid biosynthesis, glycerophospholipid and glycerolipid metabolism. The findings provide new clues in understanding the regulatory role of taurine in lipid and fatty acid metabolism of fish. It is hoped that the obtained results will help in the design of feed formulations to improve grouper growth from the perspective of aquaculture nutrition.